1994
DOI: 10.1080/09553009414551861
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Haplotyping of Ataxia-telangiectasia Families Localizes the Major Gene to an ∼ 850 kb Region on Chromosome 11q23.1

Abstract: The genotyping data given localize the major A-T gene to an approximately 850 kb region. They also localize the group A A-T gene (ATA) to a region that contains the approximately 850 kb region. They are compatible with linking A-TFresno to 11q22-23. NBS-V2 does not link to this region. Four non-linking families contain only single affecteds, suggesting that these may be spontaneous mutations rather than evidence for an A-T gene outside the 11q22-23 region. Finally, two other non-linking families contain recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…This is one of the six non-linked families in the 176 AT families used positionally to clone the ATM gene. 16,17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is one of the six non-linked families in the 176 AT families used positionally to clone the ATM gene. 16,17 .…”
Section: Resultsmentioning
confidence: 99%
“…12 The ATM gene was cloned in 1995, 13,14 following a seven-year positional cloning study by an international consortium. [15][16][17] It spans approximately 150 kb genomic DNA and contains 66 exons including alternative splicing variants. The major ATM transcript is 12 kb and the protein is correspondingly large (approx.…”
Section: Introductionmentioning
confidence: 99%
“…However, linkage studies showed only one locus on chromosome 11q23 accounting for the disease in different populations [49,50]. Mutation analysis of the ATM gene has confirmed the genetic homogeneity of A-T.…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…Following localization of the A-T gene to 850 kb on the long arm of chromosome 11 (4,5), it now appears to have been cloned (6). The surprising result is that one gene is mutated in all the complementation groups, which makes the original observations of complementation groups difficult to rationalize.…”
mentioning
confidence: 99%